2005
DOI: 10.1161/01.str.0000150668.58689.f2
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Mapping of White Matter Hyperintensities (WMH)

Abstract: Background and Purpose-MRI segmentation and mapping techniques were used to assess evidence in support of categorical distinctions between periventricular white matter hyperintensities (PVWMH) and deep WMH (DWMH

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
265
2
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 441 publications
(280 citation statements)
references
References 57 publications
12
265
2
1
Order By: Relevance
“…We did not treat periventricular and deep WMH separately, as has been done in some previous studies, because these have been shown to be highly correlated [e.g. DeCarli et al, 2005 found the correlation to be around r  =  0 .9] and their division may be arbitrary: for example, periventricular WMH are often contiguous with superior deep WMH.…”
Section: Methodsmentioning
confidence: 99%
“…We did not treat periventricular and deep WMH separately, as has been done in some previous studies, because these have been shown to be highly correlated [e.g. DeCarli et al, 2005 found the correlation to be around r  =  0 .9] and their division may be arbitrary: for example, periventricular WMH are often contiguous with superior deep WMH.…”
Section: Methodsmentioning
confidence: 99%
“…We made no distinction between deep and periventricular WML, as it has been shown that deep, periventricular, and total WML are highly correlated with each other (DeCarli et al, 2005). Furthermore, we chose to use total WML volume, as it has been suggested that categorical distinctions between periventricular and deep WML are arbitrary (DeCarli et al, 2005). According to current guidelines (Hachinski et al, 2006), WML volumes were normalized for ICV to correct for differences in head size.…”
Section: Assessment Of White Matter Lesionsmentioning
confidence: 99%
“…For example, in (Swartz, et al 2002), a 3D classification algorithm was applied to separate DWMHs from PVWMHs. Other investigators have used nonlinear image registration methods to convert the WMHs across subjects into a standard space (Taylor, et al 2003;DeCarli, et al 2005). …”
Section: Introductionmentioning
confidence: 99%